Conflicts of interest in the coastal area of Tonkin Gulf (Vietnamese part) - Cao Thi, Thu Trang; Tran, Duc Thanh; Nguyen, Van Bach (Vietnam Journal of Marine Science and Technology, 2022)
Based on the analysis of relevant information on the socio-economic development characteristics of 11 provinces and cities in the Gulf of Tonkin, ten (10) conflicts of interest have been listed, analyzed, and evaluated. Conflicts of interest are classified into conflicts between sectors, development and conservation, localities, and countries. The conflicts of interest are related to disputes on marine space and resources and negatively impact the environment. Understanding the nature of conflicts of interest in the region to have reasonable solutions, especially for antagonistic conflicts, is very important in the sustainable development of the Gulf of Tonkin.